Perancangan Sistem Rekapitulasi Data Order Menggunakan Bot Otomatis pada Layanan Indihome - Syifa Aqilah; Khairan AR (Jurnal Teknologi Informasi dan Multimedia, 2026)
This study discusses the design of a data order recap system using an automated bot for Indi-Home services from PT Telekomunikasi Indonesia (Telkom). IndiHome is a fiber optic-based communication service that provides home telephone, cable television, and internet facilities. With the growth of customers, the need for an efficient order management system becomes important because manual processes often lead to delays, recording errors, and difficulty in monitoring or-der status in real-time. A Telegram-based automated bot is proposed as a solution to automate the process of recording, reporting, and monitoring order data, thereby improving the speed, ac-curacy, and transparency of order management. The research method used is Research and De-velopment (R&D) with the stages of observation, design, creation, testing, and product validation. The evaluation results from 30 respondents, consisting of 1 team leader, 3 admins, and 26 salespeople, showed that this bot system is very effective and efficient, with a 100% success rate for the 1 team leader and 3 admins, while the trial conducted with the 26 salespeople achieved a 97.71% success rate. This system provides convenience, reduces manual errors, speeds up the follow-up process, and improves team coordination in managing IndiHome orders. Therefore, this recap bot has the potential to become the new standard in order data management.